Analisis Teori Campur Kode Pada Cuitan di Aplikasi X: Analysis of Code Mixing Theory in Tweets in Application X - Rabbani, Raihan Athiyyah; Syifa, Navila Inasis; Ananta D, Febriola Tesya; Sa’adah, Khilyatus; Ferdiansyah, Muhammad (KIRANA : Social Science Journal, 2025)
This study aims to analyze code-mixing in tweets on the X application, focusing on the trends and factors influencing the mixing of Indonesian and foreign languages, particularly English. This research uses observation and tweet sampling methods, analyzed through a descriptive qualitative approach. The analysis shows that code-mixing is often used to clarify meaning, express self-identity, and follow language trends within the digital community. Furthermore, factors such as user demographics, expression needs, and the influence of global culture affect code-mixing patterns in tweets.